Pengembangan Media Monopoli Puisi untuk Meningkatkan Kemampuan Menulis Puisi pada Siswa Kelas IV SD Negeri Karangsuno - Tsania, Alvina Nafis; Kurnianto, Bagas (Jurnal Simki Pedagogia, 2025)
The purpose of this study was to improve students' poetry writing skills, through the development of appropriate and effective learning media in the form of Monopoly Poetry media. This study applies the ADDIE R&D model method. The subjects of the study included 26 students and teachers of grade IV at SD Negeri Karangsuno, material validators, and media validators. The results of the feasibility test carried out by the material validator obtained a percentage of 90% and from the media validator obtained a percentage of 84%, both of which were included in the "Very Appropriate" criteria. This Monopoly Poetry media received a positive score from the results of the student response questionnaire with a percentage of 88.33% and teacher responses of 92% with the "Very Appropriate" criteria. When viewed from the results of the paired sample t test and the n-gain test, it can be seen that this Monopoly Poetry media is effective to use. The results of the paired sample t test obtained a Sig. (2 tailed) value of 0.00 <0.05, then H0 is rejected, while the results of the n-gain test showed a mean of 0.72 with the "High" criteria. So, the Monopoly Poetry media is appropriate and effective to use for learning to write poetry.